Analisis pendapatan pekebun kulit kayu manis (Cassiavera) di Kecamatan Bukit Kerman, Kabupaten Kerinci (studi kasus Desa Pengasi Lama) - Inisa, Azura; Junaidi, Junaidi; Bhakti, Adi (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to analyze the factors that affect the income of cinnamon bark (cassia vera) smallholders, with a case study in Pengasi Lama Village, Bukit Kerman District, Kerinci Regency. The data used are primary data sourced from a survey on cinnamon planters. The number of samples as many as 75 farmers was taken by simple random sampling. The analysis tool uses multiple regression models. The results showed that the number of plants, price, and production costs had a positive and significant effect on the income of cinnamon bark smallholders in Pengasi Lama Village